PHYSICOCHEMICAL CHARACTERISTICS OF MARTABE DRINK [PURPLE PASSION FRUIT (PASSIFLORA EDULIS VAR. EDULIS SIMS) TAMARILLO (CHYPOMANDRA BETACEAE SENDT.)] - Reno Irwanto; Raini Panjaitan; Nanda Triandita; Nela Eska Putri (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2023)
Martabe drink is a drink made from purple passion fruit and Dutch eggplant. This drink can be found easily in North Sumatra. The content of purple passion fruit and Dutch eggplant is rich in nutritional compounds, especially micronutrients and bioactive compounds. This makes the martabe drink a functional drink that not only quenches thirst and is delicious but also good for health. The high content of micro compounds in the form of vitamins and minerals, as well as bioactive compounds (antioxidants), makes it susceptible to damage. Making a martabe drink in powder form is an effort to maintain the nutritional value and essential bioactive compounds. Instant powder drinks can also increase the shelf life, simplify the distribution process and increase the ease of increasing the economic value of passion fruit and Dutch eggplant. Martabe instant drink is made using the thin layer drying (TLD) technique. This technique was chosen because it can produce powdered drinks with a reasonably high yield without reducing the nutritional value during the process and is more effective and efficient. The study used a completely randomized design (CRD) consisting of four treatments and three replications with variations in the ratio of purple passion fruit and Dutch eggplant. The results showed that the yield values ranged from 65.98-82.39%, moisture content 3.02-3.18%, pH 3.77-3.87, vitamin C content 16.91-24.04 mg/100g, and antioxidant activity of 60.78-76.38 ?g/mL.